Characterization and localization of Tb1290, a putative mitochondrial protein in Trypanosoma brucei - Knobloch, Tomáš (Jihočeská univerzita, 2019)
In this thesis methods in-situ tagging, immunofluorescence microscopy, cell fractionation are utilized for localization and RNA interference for determination of essentiality of protein Tb927.11.1290 in Trypanosoma brucei.
Characterization and localization of Tb1290, a putative mitochondrial protein in Trypanosoma brucei